2016
DOI: 10.1108/edi-04-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Equality and diversity in democracy: how can we democratize inclusively?

Abstract: Abstract. This essay explores how developing more complex analyses of power and politics sheds light on important themes for both intersectionality and participatory democracy. First of all, drawn from intersectional inquiry, the article outlines three focal points of a power analytic: how analyses of intersecting, structural oppressions underpin systems of domination; how a domains-of-power framework provides a set of conceptual tools for analyzing and responding to intersecting power relations; and how a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Application of this perspective, therefore, requires an ‘insider view’ of experiences that are characteristic of people at the particular intersection of identities in question. Within the democratic scholarship literature, Jone CMartínez-Palacios (2016) successfully applies this perspective and analyses the experiences of deaf Basque women with participatory and deliberative institutions. However, intersectional scholars have also argued in favour of applying intersectionality more broadly, as ‘a challenge [that] urges us to grapple with and overcome our entrenched perceptual-cognitive habits of essentialism, categorical purity, and segregation’ (Carastathis, 2016: 4).…”
Section: Intersectionality and Democratic Inclusionmentioning
confidence: 99%
“…Application of this perspective, therefore, requires an ‘insider view’ of experiences that are characteristic of people at the particular intersection of identities in question. Within the democratic scholarship literature, Jone CMartínez-Palacios (2016) successfully applies this perspective and analyses the experiences of deaf Basque women with participatory and deliberative institutions. However, intersectional scholars have also argued in favour of applying intersectionality more broadly, as ‘a challenge [that] urges us to grapple with and overcome our entrenched perceptual-cognitive habits of essentialism, categorical purity, and segregation’ (Carastathis, 2016: 4).…”
Section: Intersectionality and Democratic Inclusionmentioning
confidence: 99%
“…Moreover, the agendas of intersectional politics, antiracism, and decolonisation are rarely incorporated in the theory and practice of deliberative democracy and its politics of knowledge (Squires 2010;Martinez Palacios 2016). Uneven power relations persist, and continue to shape the minds, knowledge, and governance regimes of former colonial states (Ngugi 1986;Mignolo 2007;Mignolo and Walsh 2018;Fanon 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have gone further and shown that this exclusion is related to the 1. The differences among democratizing via deliberation, via participation and via community development exist both in their genealogies and in the normative conditions respecting the legitimization of the outcome, product or decision (Martínez-Palacios, 2016). However, the fact that many participatory processes available are designed based on a hybridization of the three means that the most recent theory on democratic expansion uses, as this article does, the term "democratic innovation" to refer broadly to those participatory apparatuses that seek to extend at least four democratic goods: inclusion, popular control, citizens' ability to judge public decisions, and the transparency of decision-making processes (Fung and Wright, 2003;Smith, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, because their analysis allows an inductive, experience-based and sensitive approach to the structures of power (race, gender or class among others) that intersect in the oppression experienced by those who are excluded from DIs (Martínez-Palacios, 2016). Studying the forms adopted by counterpublics makes it possible to answer the two questions, "Why do some women decide to become counterpublic?"…”
Section: Introductionmentioning
confidence: 99%